Performance of potential rice genotypes for growth and yield under alternate wetting and drying intervention - Majeed, Abid; Ahmed, Muhammad Shahzad; Siddique, Faiza; Javaid, Rana Arsalan; Abbas, Syed Haider; Zabi Ullah; Hassan, Jalal (Journal of Pure and Applied Agriculture, 2023)
Rice is a staple crop that is grown and consumed all around the globe. It is major food and cash crop of Pakistan sharing a significant position in national GDP. Rice, being an intensive water requiring crop, is facing pressure towards its cultivation due to limited water availability. In light of the current issue, water-saving technologies are needed to be improved and adopted to meet the food demand of a rapidly growing population. Alternate wetting and drying (AWD) is a method of irrigation to raise rice crop even with less irrigation water. Objective of the study was to compare the paddy yield of irrigated rice with AWD technology. The performance of 29 genotypes (hybrids, GSR lines and indigenous varieties) was assessed with two replications and three treatments of irrigation at field area of Rice Program NARC, Islamabad. The results of pooled analysis of data showed significant variation for plant height, number of productive tillers, number of grains per panicle, panicle length, thousand grain weight, days to flowering, days to maturity and paddy yield among all the genotypes. In case of yield, huge variation was observed among hybrids and Green Super Rice (GSR) lines with respect to indigenous varieties. The paddy yield of hybrids ranged between 6.5 to 9.5 kg in a plot size of 7.2 m2 while others genotypes showed paddy yield ranging around 0.5kg to 2.25 kg/7.2m2 . Paddy yield was significantly increased with reduced input cost of irrigation by implementing the AWD technique as compared to conventional method of irrigation (flooding). AWD method of irrigation is not only conserved the resources but also increased water productivity. It was concluded from this study that farmers can use AWD tube to increase their profitability with reduced irrigations. © 2021 Department of Agricultural Sciences, AIOU